The prediction value of serum anion gap for short-term mortality in pulmonary hypertension patients with sepsis: a retrospective cohort study - Zhu, Jinhua; Zhang, Zeying; Lei, Yefei; Ouyang, Zhenrong; Kutty, Shelby; Liu, Qiming; Xiao, Yunbin (Frontiers in Medicine, 2025)
BackgroundThe relationship between anion gap (AG) and short-term mortality of pulmonary hypertension (PH) patients with sepsis in the intensive care unit (ICU) remains unclear.MethodsThis study involved a retrospective analysis of incident PH patients with sepsis first admitted to the ICU in the MIMIC IV database (2008 to 2019). Short-term outcomes include in-hospital mortality and 28-day mortality. According to the AG value (17.0 mmol/L), patients were divided into high-AG and low-AG groups. The Kaplan–Meier survival curve was used to compare the cumulative survival rates of the high and low groups using the log-rank test. Multivariable Cox regression analyses were constructed to assess the relationship between AG and short-term outcomes in PH patients with sepsis.ResultsA total of 2,012 sepsis patients with PH were included. The in-hospital mortality rates (11.4%) and 28-day mortality rates (12.8%) in the high-AG group were higher than those in the low-AG group (5.0% or 7.2%, respectively; P < 0.001). The Kaplan–Meier curve showed that the in-hospital and 28-day cumulative survival rates were lower in the high-AG group than in the low-AG group (P < 0.001). The multivariable Cox regression analysis confirmed that elevated AG was an independent risk factor of in-hospital mortality, 28-day mortality, and length of stay in the ICU and hospital. The relationship between elevated AG and in-hospital mortality remains stable after subgroup analyses.ConclusionElevated serum AG is associated with increased risk-adjusted short-term mortality in PH patients with sepsis, and it may aid clinicians in identifying patients with poor prognosis as early as possible.